Synergistic effect of RHA and FCW in alkali-aggregate reaction mitigation - Guillante, Patrícia; Abreu, Aguida Gomes de; Kulakowski, Marlova Piva; Mancio, Maurício; Kazmierczak, Claudio de Souza (Ambiente Construído, 2019)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="IT">Pozzolans rich in silica, such as Rice Husk Ash (RHA), contribute to compressive strength gain but at the same time might increase alkali-aggregate reaction (AAR) in mortar mixtures. Pozzolans that have aluminates, such as Fired Clay Brick Waste (FCW), can be efficient to mitigate AAR but tend to lead to a slower compressive strength development. The association of different types of pozzolans, however, may result in a synergistic effect, compensating individual deficiencies. This paper presents a study of mixtures containing RHA, FCW and these two materials combined, aiming to obtain benefits in the mechanical behavior and in the durability regarding AAR. A substitution rate of 20% Portland cement by pozzolanic material was used. Through accelerated AAR tests and compressive strength measurements, it was found that while RHA is considered harmful to AAR – even when using an innocuous aggregate – FCW presents benefits, also avoiding this deleterious effect when combined with RHA. The same occurs in the compressive strength development, where RHA compensates a small loss of compressive strength associated with the use of FWC alone.